2020
DOI: 10.3390/md18120647
|View full text |Cite
|
Sign up to set email alerts
|

Improved Isolation Procedures for Okadaic Acid Group Toxins from Shellfish (Mytilus edulis) and Microalgae (Prorocentrum lima)

Abstract: Okadaic acid (OA) group toxins may accumulate in shellfish and can result in diarrhetic shellfish poisoning when consumed by humans, and are therefore regulated. Purified toxins are required for the production of certified reference materials used to accurately quantitate toxin levels in shellfish and water samples, and for other research purposes. An improved procedure was developed for the isolation of dinophysistoxin 2 (DTX2) from shellfish (M. edulis), reducing the number of purification steps from eight t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Aromatic HP20 resin was used to adsorb the GYMs from the culture medium comprising the fragmented K. selliformis or A. ostenfeldii cells due to its ability to adsorb toxins from the seawater [7,24]. Additionally, HP20 resin was also applied to enrich other lipophilic toxins (AZA1, AZA2, OA, DTX1) that had been released into the culture medium [32,33]. In this study, SPATT bags containing HP20 resin were placed in the culture medium to absorb GYM-A for 24 h in order to evaluate its adsorption capacity.…”
Section: Comparison Of Different Techniques For Harvesting Gymsmentioning
confidence: 99%
“…Aromatic HP20 resin was used to adsorb the GYMs from the culture medium comprising the fragmented K. selliformis or A. ostenfeldii cells due to its ability to adsorb toxins from the seawater [7,24]. Additionally, HP20 resin was also applied to enrich other lipophilic toxins (AZA1, AZA2, OA, DTX1) that had been released into the culture medium [32,33]. In this study, SPATT bags containing HP20 resin were placed in the culture medium to absorb GYM-A for 24 h in order to evaluate its adsorption capacity.…”
Section: Comparison Of Different Techniques For Harvesting Gymsmentioning
confidence: 99%
“…In agreement with the current study, several studies of Dinophysis cultures and blooms have indicated that a high proportion of the OA/DTXs can be in the esterified form (Deeds et al, 2020; Miles et al, 2006) as is also often the case for OA/DTX‐producing Prorocentrum spp. (Hu et al, 1992; Kilcoyne et al, 2020; Suárez‐Gómez et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A pellet of P. lima (CCMI-1036, isolated from southwest Ireland) was generated in studies carried out by Kilcoyne et al [ 14 ]. The contents of a cell stack (~2 L) were filtered through a 20 µm mesh, and the biomass was transferred into a 50 mL centrifuge tube.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, regulatory limits are in place in many countries for 1 – 3 and their esterified forms in shellfish harvested for human consumption [ 4 , 5 , 6 ]. A range of other OA/DTX derivatives has been identified in dinoflagellates, including esters of 1 – 3 at C-1 [ 7 , 8 , 9 ], 7-deoxyOA ( 7 ) [ 10 , 11 ], and 19-epimers of OA and DTX2 [ 12 , 13 ], although the latter appear to be artefacts of extraction and isolation [ 14 ]. The metabolism of OA/DTXs in shellfish leads to extensive conversion to 7- O -acyl fatty acid esters [ 15 ] which, although appearing to be of somewhat reduced toxicity [ 16 ], are believed to be largely converted back to the free toxins during digestion [ 15 ] and are therefore included in the regulatory framework by including a base-hydrolysis step during sample preparation [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%